Human evolution a multimedia guide to the fossil record - Walker, Phillip L. 1947- (W.W. Norton, 2000)
This CD-ROM presents 3-D, photo-realistic images of fossils to teach students about ten important milestones in human evolution, from the appearance of the primates to the demise of the neanderthals. Students can rotate over 30 fossil and modern skulls, bones, and artifacts, viewing them from any angle. Includes illustrated definitions of all technical terms